Influence of Different Protocols of Urethral Catheterization after Pharmacological Induction (Ur.Ca.P.I.) on Semen Quality in the Domestic Cat. Issue 6 (20th October 2015) - Cunto, M; Küster, DG; Bini, C; Cartolano, C; Pietra, M; Zambelli, D
Contents: The aim of this study was to evaluate the influence that different protocols of urethral catheterization after pharmacological induction (Ur.Ca.P.I.) may have on the semen quality of the domestic cat. The study has been divided into two experiments: one in which different dosages of medetomidine administrated are evaluated and the second one in which the timing of the catheterization after pharmacological induction is tested. In the first experiment, 18 cats were sedated with the recommended dosage of medetomidine (130 μg/kg i.m.) while the other 18 were sedated with a lower dose of the same drug (50 μg/kg i.m.). In the second experiment, three groups were implemented, each containing 25 subjects. In group 1, the semen collection was performed immediately once the pharmacological effect of the drug was reached; in group 2, the semen collection was performed three times every 5 min after the pharmacological effect was reached; finally, in group 3, Ur.Ca.P.I. was performed 20 min after the pharmacological effect was reached. All the different protocols permitted sperm collection, nevertheless the first experiment showed a better quality in terms of volume, concentration, total number of spermatozoa (p < 0.01) and quality of the movement (motility p < 0.05 and forward progressive motility p < 0.01), using a high medetomidine dosage rather than 50 μg/kg i.m. In the second experiment, forward motility was statistically higher (p < 0.01) in the first group and total volume was higher (p < 0.01) in the second and third group, while other parameters were statistically not different. Results suggest that a single catheterization immediately after the onset of the pharmacological effect leads to a good‐quality semen with the lowest possibility of damaging the urethra and that a sedation with 130 μg/kg of medetomidine leads to a better quality sperm collection than 50 μg/kg does.